Science Skepticism Across 24 Countries. Issue 1 (January 2022) - Rutjens, Bastiaan T.; Sengupta, Nikhil; der Lee, Romy van; van Koningsbruggen, Guido M.; Martens, Jason P.; Rabelo, André; Sutton, Robbie M.
Efforts to understand and remedy the rejection of science are impeded by lack of insight into how it varies in degree and in kind around the world. The current work investigates science skepticism in 24 countries ( N = 5, 973). Results show that while some countries stand out as generally high or low in skepticism, predictors of science skepticism are relatively similar across countries. One notable effect was consistent across countries though stronger in Western, Educated, Industrialized, Rich, and Democratic (WEIRD) nations: General faith in science was predicted by spirituality, suggesting that it, more than religiosity, may be the 'enemy' of science acceptance. Climate change skepticism was mainly associated with political conservatism especially in North America. Other findings were observed across WEIRD and non-WEIRD nations: Vaccine skepticism was associated with spirituality and scientific literacy, genetic modification skepticism with scientific literacy, and evolution skepticism with religious orthodoxy. Levels of science skepticism are heterogeneous across countries, but predictors of science skepticism are heterogeneous across domains.